Influence of the clindamycin administration route on the magnitude of clindamycin–rifampicin interaction: a prospective pharmacokinetic study. (December 2021) - Zeller, Valérie; Magreault, Sophie; Heym, Beate; Salmon, Dominique; Kitzis, Marie-Dominique; Billaud, Eliane; Marmor, Simon; Jannot, Anne-Sophie; Salomon, Laurence; Jullien, Vincent
Abstract: Objectives: An important clindamycin–rifampicin pharmacokinetic (PK) interaction has been reported, but the potential influence of the clindamycin administration route on that interaction is unknown. This prospective, observational, comparative PK study was undertaken to characterize and analyse the impact of the route, comparing the rifampicin enzyme-inductor effects on clindamycin clearance ( CLclin ) for oral versus intravenous (IV) administration. Methods: Patients with bone-and-joint infections (BJIs) were treated with clindamycin monotherapy ( n  = 20) or clindamycin–rifampicin combination therapy ( n  = 19). Patients received continuous IV clindamycin infusion for 2–6 weeks, followed by an oral regimen. Liquid chromatography–mass spectrometry was used to measure plasma clindamycin concentrations at the end of IV and after 2 weeks of oral treatment. The ratios of the mean CLclin for the combination and monotherapy groups were calculated for IV ( Riv ) and oral ( Rpo ) routes, with the final ratio, Rf  =  Rpo / Riv, representing the fold change of the rifampicin-inducing effect from the IV to the oral route. Results: Comparing monotherapy with combination-therapy groups, the former's median steady-state concentration was two-fold higher after IV administration (8.49 versus 3.82 mg/L, p < 0.001) and its median AUC 0–8h was 12 times higher after oral intake (37.7 versus 3.1 mg.h/L, p < 0.001). Riv, Rpo and Rf were 2.68, 18.8 and 7.0 respectively. Conclusion: The magnitude of this interaction was markedly increased by oral intake, questioning the use of oral treatment for difficult-to-treat infections like BJIs. Nevertheless, the clindamycin–rifampicin combination seems possible provided that clindamycin is administered by continuous IV infusion.